2018
DOI: 10.3389/fvets.2018.00045
|View full text |Cite
|
Sign up to set email alerts
|

Prepartum Maternal Behavior of Domesticated Cattle: A Comparison with Managed, Feral, and Wild Ungulates

Abstract: The event of giving birth is an essential part of animal production. In dairy cattle production, there are substantial economical and welfare-related challenges arising around the time of parturition, and hence increased focus on efficient management of the calving cow. Drawing on the research literature on prepartum maternal behavior, this review compares cattle to other members of the ungulate clade with the aim of understanding the biological basis of bovine prepartum behavior with main emphasis on dairy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 108 publications
(171 reference statements)
2
55
1
Order By: Relevance
“…In that study, a comparison between the different dairy farms showed that a high efficiency of food conversion by animals was more effective in terms of environmental impact and, above all, in the production of greenhouse gases and the use of non-renewable energy. Therefore, aspects such as animal welfare, for example in extensive livestock management (more space available, access to pasture, quantity and quality of fresh forage, air quality) (67,68), could indirectly affect the environmental impact by operating on animal efficiency. At the same time, fresh forage may lead to a greater food conversion index and food efficiency (69), providing a positive impact on greenhouse gas emissions and on the environmental influence of livestock farming (70).…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…In that study, a comparison between the different dairy farms showed that a high efficiency of food conversion by animals was more effective in terms of environmental impact and, above all, in the production of greenhouse gases and the use of non-renewable energy. Therefore, aspects such as animal welfare, for example in extensive livestock management (more space available, access to pasture, quantity and quality of fresh forage, air quality) (67,68), could indirectly affect the environmental impact by operating on animal efficiency. At the same time, fresh forage may lead to a greater food conversion index and food efficiency (69), providing a positive impact on greenhouse gas emissions and on the environmental influence of livestock farming (70).…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Near to calving, seminaturally housed cattle will seek isolation from the herd ( Lidfors et al, 1994 ). This is similar to dairy cattle housed in confinement, though it is speculated that calving difficulty ( Rørvang et al, 2017 ) and social rank and personality ( Rørvang et al, 2018a ) influence access to calving in a private area. Cattle’s desire to seek social isolation prior to calving has been referred to in a “hider-follower” paradigm (as reviewed by Rørvang et al, 2018b ).…”
Section: Conventional Calf-raising Practices Compared To In Naturementioning
confidence: 74%
“…In free-range or semi-natural conditions, a cow separates herself from the herd before calving (see Rørvang et al ., 2018 for review). The calf hides for some days (Reinhardt et al ., 1977; Vitale et al ., 1986) and the dam prevents the members of the herd from interacting with her calf (Reinhardt, 1980).…”
Section: Cow-calf Contact Phasesmentioning
confidence: 99%